2013
DOI: 10.1152/ajpregu.00231.2013
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-induced diaphragm dysfunction: cause and effect

Abstract: Powers SK, Wiggs MP, Sollanek KJ, Smuder AJ. Ventilator-induced diaphragm dysfunction: cause and effect. Am J Physiol Regul Integr Comp Physiol 305: R464 -R477, 2013. First published July 10, 2013 doi:10.1152/ajpregu.00231.2013 is used clinically to maintain gas exchange in patients that require assistance in maintaining adequate alveolar ventilation. Common indications for MV include respiratory failure, heart failure, drug overdose, and surgery. Although MV can be a life-saving intervention for patients suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
156
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 122 publications
4
156
2
8
Order By: Relevance
“…These are proteases that target the myofilaments leading to atrophy and diaphragm weakness (43). In the current study, no evidence of proteolysis was found in the myofilament proteins isolated from the diaphragm preparations from the 18 wk TAC and 18 wk AMI groups, nor was there loss of in vitro force generation in the 18 wk TAC and 18 wk AMI groups.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…These are proteases that target the myofilaments leading to atrophy and diaphragm weakness (43). In the current study, no evidence of proteolysis was found in the myofilament proteins isolated from the diaphragm preparations from the 18 wk TAC and 18 wk AMI groups, nor was there loss of in vitro force generation in the 18 wk TAC and 18 wk AMI groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have demonstrated that mechanical ventilation can increase the activity of calpain and caspase-3 in the diaphragm (for review, see 43). These are proteases that target the myofilaments leading to atrophy and diaphragm weakness (43).…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary findings suggest that intermittent phrenic nerve stimulation preserves human diaphragm fiber contractile function, possibly by inhibiting proteolysis and/or posttranslational modification of sarcomeric proteins seen after MV (3,10). However, the protection does not appear to be mediated by changes in protein carbonyls or ubiquitination.…”
mentioning
confidence: 68%
“…The first animal study of this issue was reported in 1994, and further such studies have since been performed [1]. The first prospective study indicated that controlled MV resulted in diaphragmatic muscle atrophy and contractile dysfunction in rats; this study showed that controlled MV for 48 hours without spontaneous breathing results in a significant decrease in diaphragm muscle mass and also a significant reduction in maximal diaphragmatic specific force production [10].…”
Section: Discussionmentioning
confidence: 94%
“…The indications for MV are respiratory failures of various etiologies, including chronic obstructive pulmonary disease, status asthmaticus, and/or heart failure, acute drug overdose, neuromuscular diseases, sepsis, and during the perioperative periods [1]. In the USA, more than 300,000 patients receive prolonged MV each year in intensive care units (ICU) [2], and it seems like that the number of patients who needs MV is increasing in Korea, however, the exact data is not in the literature.…”
Section: Introductionmentioning
confidence: 99%